CLASSIFICATION MODEL OF C++ COURSE IN E-LEARNING ENVIRONMENT - ABUZİR, Yousef (The Eurasia Proceedings of Educational and Social Sciences, 2016)
E-learning grows rapidly and it draws the attention to an important shift in the educational paradigm. This research tries to propose and design an intelligent e-Learning environment for students in which classification techniques and user profiles play the role of an automatic interactive classification system. This system will simplify the task of finding the learning materials and related topics. Our research discusses how specific concepts of the theories of indexing, classifying, retrieving and consultation of a collection of learning materials based on student profiles might support various instructional functions of e-Learning. In this research, we conduct an experiment that carried out on educational materials for C++ Language. Such an experiment has very special features, which make it different from other approaches by using thesaurus as a tool for classification. It is important to evaluate the effectiveness and efficiency of our approach. The experimental results illustrate an overall performance of classification techniques, having 88% of correctly classiﬁed.